Local Arctic Air Pollution: A Neglected but Serious Problem. Issue 10 (3rd October 2018) - Schmale, J.; Arnold, S. R.; Law, K. S.; Thorp, T.; Anenberg, S.; Simpson, W. R.; Mao, J.; Pratt, K. A.
Abstract: Air pollution in the Arctic caused by local emission sources is a challenge that is important but often overlooked. Local Arctic air pollution can be severe and significantly exceed air quality standards, impairing public health and affecting ecosystems. Specifically in the wintertime, pollution can accumulate under inversion layers. However, neither the contributing emission sources are well identified and quantified nor the relevant atmospheric mechanisms forming pollution are well understood. In the summer, boreal forest fires cause high levels of atmospheric pollution. Despite the often high exposure to air pollution, there are neither specific epidemiological nor toxicological health impact studies in the Arctic. Hence, effects on the local population are difficult to estimate at present. Socioeconomic development of the Arctic is already occurring and expected to be significant in the future. Arctic destination shipping is likely to increase with the development of natural resource extraction, and tourism might expand. Such development will not only lead to growth in the population living in the Arctic but will likely increase emission types and magnitudes. Present‐day inventories show a large spread in the amount and location of emissions representing a significant source of uncertainty in model predictions that often deviate significantly from observations. This is a challenge for modeling studies that aim to assess the impacts of within Arctic air pollution. Prognoses for the future are hence even more difficult, given the additional uncertainty of estimating emissions based on future Arctic economic development scenarios. Key Points: Local Arctic air pollution is among the most severe world wide Arctic meteorological conditions exacerbate air pollution and create unique pollution formation mechanisms Future economic activities in the Arctic are expected to increase local air pollution